A longitudinal study of antibody levels in an area of low malaria endemicity using the Indirect Fluorescent Antibody (IFA) technique - Pasay, Ma. Cielo J.
Little is known about the dynamics of antibody responses among residents of villages with low endemic malaria. A longitudinal study was conducted in the low endemic municipality of Morong, Bataan, Philippines to provide baseline information on the antibody responses to the malarial parasites using the Indirect Fluorescent Antibody Technique (IFAT). A total of 125 individuals who were initially positive for malaria parasites by blood smear were followed up for 9 months at 3 month - intervals. Fingerprick blood was collected for the standard thick and thin smears and for serology. The IFA technique was used to detect malaria antibodies particularly of the isotypes IgM and IgG. The cases were also examined for malaria associated symptoms at the time of follow-up. Results showed that on the initial survey, 87 of the study population had no detectable IgM antibodies while 99.2 had IgG titers of 1:64 and above. When followed-up, fluctuations in IgM and IgG were seen suggesting the presence of active transmission on the 3rd and 6th month of follow-up. The infection rate as determined by parasite detection in blood smears of the study population was 11 for 3 follow-up periods but geometric mean IgG antibody titers ranged from 1:256 - 1:16, 384 in areas where no parasitemic cases were seen, indicating potential for transmissio. IgM and IgG values tended to be higher in samples from patients that were infected than those not infected, and this trend was significant (p 0.05 and p 0.01 for IgM and IgG, respectively). These suggest a probable association between positivity of malarial smear and antibody levels. The IFA responses was higher among adults than among children, reflective of past malaria episodes in the study population. The presence of high IgG levels (1:4096) detected did not seem to prevent infection with either Plasmodium falciparum or P. vivax but appeared to be negatively associated with symptoms.
Thesis (Master of Science in Public Health, Parasitology)--University of the Philippines Manila.
Keywords: Malaria; Fluorescent antibody technique